Strategi Pengembangan Produk Olahan Buah Mangga Gedong Gincu (Mangifera Indica L.) Berupa Fruit-Strips (Studi Kasus di PT Saudagar Buah Indonesia) - Afifah, Salma; Renaldi, Eddy (Universitas Galuh, 2024)
This research aims to identify several alternative strategies for developing processed products from Gedong Gincu Mangoes, specifically fruit-strips, at PT Saudagar Buah Indonesia, in order to expand their market sales. The research utilizes various analytical tools, including SWOT analysis and QSPM analysis. The method employed in this study is qualitative, using primary data such as observations and interviews, as well as secondary data in the form of literature and scientific journals. Based on the research findings, it can be concluded that the strengths of PT Saudagar Buah Indonesia in business development lie in effective communication among members, while the weakness lies in the level of employee wages. The main opportunities for PT Saudagar Buah Indonesia in business development are the advantages of utilizing technology in company activities, while the main threats include research and development activities of other companies and price competition from competitors. Based on the SWOT and QSPM analyses conducted, the highest-scoring alternative strategy that needs to be implemented is to optimize the company's resources, allowing for better control over the company's budget allocation.